Soil distribution and soil properties in the subalpine region of Kazbegi; Greater Caucasus; Georgia - Hanauer, Thomas; Justus Liebig University Giessen (My University, 2024)
Due to their characteristic properties, mountain soils require appropriate management when used for agriculture or pasture, even when climatic conditions are favorable. To enable sustainable agricultural use, the soils of the Kazbegi district in the Mtskheta-Mtianeti region (Georgia), which located in the eastern part of the Greater Caucasus, were mapped in 2014 and 2015 and evaluated according to the Müncheberg Soil Quality Rating (M-SQR). The soils developed mainly on sedimentary fans and on glacial and fluvial sediments. They are characterized by a low to medium yield potential, with the most productive soils being found on volcanic plateaus. Fluvisols (or at least soils with fluviatile properties) are widespread in the river valleys, and bogs, histosols, also occur in the valley bottoms. Medium to very deep Cambisols or Umbrisols form on volcanic substrates. Cambisols are common on moraines, and Regosols and Cambisols are particularly common on the clayey and silty sedimentary rocks of the Jura, characterized by a high proportion of coarse fraction. The cambic horizon is not visually recognizable in these, but is clearly detectable analytically. Depending on slope inclination and exposure, Leptosols occur on the slopes and summits of sedimentary or volcanic rock. Despite this great diversity of terrestrial and semi-terrestrial soils, a high humus content, at least in the topsoil, is characteristic of all of them. No inorganic or organic contamination was detected in relevant concentrations. However, P-sorption, mainly on amorphous Al- and Fe-oxides, could lead to increased fertilizer requirements. Due to poor accessibility, most of these soils are currently only used as pasture land. Soils on fluvial deposits, especially Fluvisols, show a very high range of M-SQR values. Based on these results, a synthetic soil map was created combining geological and geodetic data as well as field mapping data to create a land use-management tool. Overall, the soils of the study area have the untapped potential to optimize the basic supply of the local population as well as tourism through the cultivation of cereals. Nevertheless, variety trials on different soil-forming substrates and erosion control are important prerequisites for the successful implementation of new cultivation systems in the region. In addition, particularly rare soils, e.g. Cambisols on tephra,should be protected. The most limiting factors from an agricultural point of view are the climate and the slope, while the low nutrient supply and low soil-pH can be counteracted by appropriate fertilization and liming.
Keywords: subalpine soils; Caucasus; ddc:630